Enhanced Oral Efficacy of Semaglutide via an Ionic Nanocomplex with Organometallic Phyllosilicate in Type 2 Diabetic Rats - Gyu Lin Kim; Jae Geun Song; Hyo-Kyung Han (MDPI AG, 2024)
This study aimed to develop an effective oral formulation of semaglutide, a glucagon-like peptide-1 receptor agonist, using an organometallic phyllosilicate-based colonic delivery system. The core nanocomplex (AMP-Sema) of 3-aminopropyl-functionalized magnesium phyllosilicate (AMP) and semaglutide was prepared via electrostatic interactions. Subsequently, AMP-Sema was coated with a polymer showing pH-dependent solubility (Eudragit® S100) for preferential colonic delivery. The surface-coated nanoparticles (EAMP-Sema) showed a narrow size distribution, and the encapsulated semaglutide maintained its conformational stability. The pH-dependent drug release property of EAMP-Sema yielded around 20% and 62% drug release at pH 1.2 and 7.4, respectively. The nanoparticles exhibited significantly decreased size and surface charge at pH 7.4, which indicated the pH-dependent dissolution of the coating layer. Furthermore, EAMP-Sema effectively improved the membrane permeability and metabolic stability of semaglutide in the gastrointestinal tract. It protected the encapsulated drugs from proteolysis in simulated intestinal fluids and increased drug transport by 2.5-fold in Caco-2 cells. Consequently, orally administered EAMP-Sema (equivalent to 8 mg/kg of semaglutide) showed significant therapeutic benefits, yielding effective glycemic control and weight loss in high-fat diet/streptozotocin (40 mg/kg)-induced type 2 diabetic rats. These results demonstrate that EAMP-Sema could improve the efficacy of orally administered semaglutide by enhancing the GI stability and cellular uptake of protein drugs.